Effect of occlusal anatomy of CAD/CAM feldspathic posterior crowns in the stress concentration and fracture load - Borges, Alexandre Luiz Souto [UNESP]; Tribst, João Paulo Mendes [UNESP]; de Lima, Aline Lins [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Özcan, Mutlu (Wiley, 2021)
Objectives: This study evaluated the effect of restoration occlusal design on the maximum fracture load and stress distribution of a feldspathic ceramic crown. Materials and Methods: Twenty dentin analogues were used to simulate a full-crown preparation. Next, 20 feldspathic crowns were milled according to the occlusal design parameter available in the CAD database (Young or Adult). The crowns were cemented with dual cure resin-cement and loaded until fracture at 1 mm/min crosshead speed. Data were analyzed by using one-way ANOVA and Tukey tests (p < 0.05). The same geometry and experimental setup was modeled and exported to the computer aided engineering software and tensile stress concentration was calculated using the finite element method with 300 N occlusal load simulation. Results: The occlusal anatomy significantly influenced the load-to-fracture (p < 0.05). Adult design showed higher mean values (1149 ± 201 N) than Young design (454 ± 77 N). The maximum principal stress criteria showed similar stress pattern for both designs, however, the highest stress concentration was calculated for Young design (91 MPa) in the occlusal surface. Conclusions: An anatomy design with reduced cusp angulation and less evident occlusal sulcus can reduce the stress concentration and increase the fracture load for feldspathic CAD/CAM posterior crowns.
Keywords: CAD/CAM; crown; finite element analysis; mandibular molar; stress